TAIGA-MOUNTAIN ANDRONOID COMPLEX OF USTJE KOZHUKHA 1 SITE - I. V. Kovtun; A. V. Fribus; S. V. Bashtannik; V. N. Zharonkin (Вестник Кемеровского государственного университета, 2015)
The paper focuses on Andronoid materials located at Ustje Kozhukha 1 site in the northern spurs of Kuznetskiy Alatau. Basing on the analysis of ceramics complexes, the authors prove a number of analogies that help define the lower date of Andronoid peoples inhabiting this area: middle – early 2nd millennium BC. The paper reconstructs the specific model of interaction between the peoples inhabiting the forest-steppe and taiga-mountain regions of Kuznetsk Alatau in the Late Andronovo period.